Western power relations against the East in the Code Geass anime series - Wijaya, Michael Janshen; Puspitasari, Diana; Suryadi, Yudi (Universitas Dian Nuswantoro, 2023)
The aim of the research is to identify four power relations of the West over the East in the anime series Code Geass: Lelouch of the Rebellion by using postcolonial studies, namely Edward Said's concept of Orientalism. This type of research is qualitative descriptive research. This study used observing and note-taking techniques in the data collection process. Data analysis in this study consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the four power relations of the West over the East are present in the form of British power over Japan. The first is political power, shown by Britannia as the ruler of Japan. Second, intellectual power is demonstrated by the influence of the Britannia media in portraying Eleven in a bad image. The three cultural powers, shown by the influence of Britannia positioned themselves as a party capable of modernizing Japan. The four moral powers are demonstrated by the form of criticism of a Prince of Britannia who saw the resistance carried out by the Japanese. The conclusion is the influence of the most incredible power is political power through Britannia which affects the lives of Japanese people in New Japan/Area 11.